Antibacterial Activity of Lauripure In vitro and on Skin of Processed Broilers - Mansour, Elwaleed; Hinton , Arthur; Reddy, P. Gopal (International Journal of Poultry Science, 2013)
Studies were conducted to examine the ability of LauriPure to inhibit the growth of Salmonella Typhimurium, Escherichia coli, Staphylococcus simulans and Listeria innocua isolates recovered from processed broiler carcasses. In vitro studies were conducted using the Bioscreen C Microbiology Reader to measure the growth of isolates during incubation at 37°C for 48 h in Tryptic Soy Broth (TSB) supplemented with 0.0, 0.5, 1.0, or 2.0% (vol/vol) LauriPure. Also, the ability of LauriPure to reduce bacterial contamination of skin from processed broilers was examined by comparing the number of bacteria recovered from skin after 3 consecutive 1 min washes in distilled water or 1.0% LauriPure solutions. After each wash, bacteria recovered from the skin were enumerated by plating skin rinsates on Eosin Methylene Blue (EMB), Staphylococci (STA) and Plate Count (PC) agars and incubating plates at 37°C for 24-48 h. Results of in vitro experiments indicated that after 48 h of incubation the optical density (OD600) of all isolates was significantly (p